2007
DOI: 10.1504/ijkl.2007.016704
|View full text |Cite
|
Sign up to set email alerts
|

Weblogs and internal communication in a corporate environment: a case from the ICT industry

Abstract: Innovations in web-based technology have generated new channels for communicative purposes. Blogs provide organisations a unique opportunity for informal knowledge sharing. However, much on the current research on blogs has a normative orientation and a focus on tools rather than the related social and communicative issues. Our theoretical approach is internal communication, which we link with the characteristics of this emerging form of social software. Based on our case, we analyse the factors affecting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 13 publications
0
13
0
2
Order By: Relevance
“…While weblogs may serve as a new medium for corporate communication (Kosonen et al 2007;Efimova and Grudin 2007;Stocker et al 2008), wikis facilitate the collaborative creation of content in the enterprise (Grace 2009;Hasan and Pfaff 2006;Watson and Harper 2008). Wikis may form suitable platforms to support identification, acquisition, development, distribution, preservation, and use of knowledge within the enterprise, which are the 'knowledge management building blocks' of Probst et al (2000).…”
Section: Introductionmentioning
confidence: 99%
“…While weblogs may serve as a new medium for corporate communication (Kosonen et al 2007;Efimova and Grudin 2007;Stocker et al 2008), wikis facilitate the collaborative creation of content in the enterprise (Grace 2009;Hasan and Pfaff 2006;Watson and Harper 2008). Wikis may form suitable platforms to support identification, acquisition, development, distribution, preservation, and use of knowledge within the enterprise, which are the 'knowledge management building blocks' of Probst et al (2000).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge blog: hosted by experts who share an interest in a specific professional topic and wish to document the knowledge Henttonen & Ellonen 2007). As more information is added to the internal knowledge base, it becomes more likely that the answer to any given question will exist (Yardi, Golder & Brzozowski 2009).…”
Section: Types Of Internal Blogs Includementioning
confidence: 99%
“…Based on multiple studies that have shown that organizations with experience in blogging are more prone to engaging in web interactivity (Kosonen et al, 2007;Raghavan, 2006), the researchers reasoned that organizations used to communicating with key publics through this highly interactive format might better incorporate the dialogic principles into their traditional web sites.…”
Section: Rq1mentioning
confidence: 99%